2023
DOI: 10.1152/ajpgi.00251.2022
|View full text |Cite
|
Sign up to set email alerts
|

A leaky human colon model reveals uncoupled apical/basal cytotoxicity in early Clostridioides difficile toxin exposure

Abstract: Clostridioides difficile (C. difficile) toxins A (TcdA) and B (TcdB) cause antibiotic-associated colitis in part by disrupting epithelial barrier function. Accurate in vitro models are necessary to detect early toxicity kinetics, investigate disease etiology, and develop preclinical models for new therapies. Properties of cancer cell lines and organoids inherently limit these efforts. We developed adult stem cell-derived monolayers of differentiated human colonic epithelium (hCE) with barrier function, investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Another recent study confirmed our observations of a barrier defect after exposure to TcdA or TcdB [42]. In this study, the redistribution of ZO-1 within the monolayer was held solely responsible for the measured barrier dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Another recent study confirmed our observations of a barrier defect after exposure to TcdA or TcdB [42]. In this study, the redistribution of ZO-1 within the monolayer was held solely responsible for the measured barrier dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…To measure cellular uptake of EV TAT‐GFP , Caco‐2 cells (1 × 10 5 ), a cell line derived from colon tumour with physiological similarity to small intestine (Ok et al., 2023 ), were seeded and cultured in 24‐well plates (Corning, USA) for 24 h. Free TAT‐GFP (20 µg), DiR‐labelled EV (60 µg) and EV TAT‐GFP (60 µg EV and 20 µg TAT‐GFP) after or before digestion in the simulated gastrointestinal fluid were added to cells, followed by incubation for 24 h. Cellular uptake and localization of EV TAT‐GFP , EV or TAT‐GFP were analysed by flow cytometry (FACSVerse, BD, USA) and confocal fluorescence microscope (FV1000, Olympus, Japan), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Liberated crypts were expanded as a monolayer on a neutralized collagen hydrogels. Crypts were placed on the top of 1 mg/mL collagen hydrogels (1 ml into each well of 6-well plate) at a density of 10,000 crypts/well, overlaid with 3 mL of Expansion Media (EM) 61 containing 10 mmol/L Y-27632 (S1049; SelleckChem, Houston, TX), and incubated at 37 °C in 5% CO 2 . EM was used to expand the epithelial cell numbers as monolayers; media was changed the day after seeding and every 48 hours afterwards.…”
Section: Methodsmentioning
confidence: 99%
“…EM was used to expand the epithelial cell numbers as monolayers; media was changed the day after seeding and every 48 hours afterwards. When the cell coverage was greater than 80% (typically 4 to 6 days), the epithelium was dissociated to fragments 62 to seed onto either 6-well tissue-culture plates coated with collagen hydrogels for continued expansion, or onto 12-well Transwell inserts (3460; Corning, Corning, NY) coated with 1% Matrigel for experiments 61 . To generate differentiated enterocytes for the toxicity assays, 2 wells of a 6-well colonic ISC expansion plate, where cells were ~90% confluent, were dissociated 61 as described above and plated on 12-well transwell inserts coated with 1% Matrigel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation